Trade promotion & consumer promotion for LG part of the marketing lab: “marketing plan to increase LG TV’s product category premium perception by end consumers” - Yan, Rian (2022)
The current challenge for LG is its low premium position in the Portuguese TV market. LG must adapt its segmentation, targeting, and positioning (STP); brand identity; and marketing mix to the specific demands and preferences of the Portuguese premium target. This paper will mainly discuss possible strategies that LG could implement among its channel members and end consumers so that the communication effect could be converted into sales. Keywords: LG, Portugal, Premium Perception, Upgrade Positioning, TV market, Re-Positioning, Channel Marketing, Trade Promotion, Consumer Promotion, In-store Display, Omnichannel Strategy